2005
DOI: 10.1016/j.jacc.2005.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Circumferential Pulmonary Vein Isolation Using a Novel Cryothermal Balloon Ablation System

Abstract: This novel cryothermal balloon ablation system is effective for isolating PVs, but injury to the right phrenic nerve was noted in this early experience. Further studies are needed to assess the long-term efficacy and safety of this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
141
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 190 publications
(144 citation statements)
references
References 21 publications
1
141
1
1
Order By: Relevance
“…536,903,1017,1182,1183,1184,1185 The right PN is most commonly affected, given it descends in close proximity to sites of ablation in the SVC and both right-sided PVs (Figure 1). 536,903,1184,1185,1187 It courses slightly further from the RIPV so that injury during treatment of this vein is less common than that occurring with RSPV ablation. PN palsy is observed with all technologies for AF ablation, including RF, cryoablation, ultrasound, and laser ablation.…”
Section: Section 10: Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…536,903,1017,1182,1183,1184,1185 The right PN is most commonly affected, given it descends in close proximity to sites of ablation in the SVC and both right-sided PVs (Figure 1). 536,903,1184,1185,1187 It courses slightly further from the RIPV so that injury during treatment of this vein is less common than that occurring with RSPV ablation. PN palsy is observed with all technologies for AF ablation, including RF, cryoablation, ultrasound, and laser ablation.…”
Section: Section 10: Complicationsmentioning
confidence: 99%
“…PN palsy is observed with all technologies for AF ablation, including RF, cryoablation, ultrasound, and laser ablation. 490,536,903,1017,1182,1183,1184,1185,1187 PN palsy can be asymptomatic or can cause dyspnea, tachypnea, cough, hiccups, and thoracic pain. The diagnosis is suggested when newly elevated hemidiaphragm with atelectasis of the ipsilateral lung base is observed on postprocedure chest radiograph.…”
Section: Section 10: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially described in the early animal studies by Sarabanda et al, phrenic nerve palsy (PNP) has proven to be the most frequently observed complication with CBA, occurring in approximately 6% of clinical procedures (range 3-11%) [11,22,23]. While PNP can be observed after AF ablation regardless of the energy source, it occurs disproportionately more frequently with balloon-based ablation technologies when compared to conventional RF ablation [7,9,10].…”
Section: Safety Of Cryoballoon Ablationmentioning
confidence: 99%
“…While the observed early excess of PNP with the 23 mm CBA cannot be denied, it is important to note that the exclusive use of larger balloons has not entirely eliminated this complication. "Over-sizing" the balloon within the RSPV may result in: 1) mechanical distortion of the RSPV orifice with an even greater shortening of the relative distance between the cryoballoon and phrenic nerve, and 2) physical impingement of the phrenic nerve with resultant palsy [23]. …”
Section: How To Perform Cryoballoon Ablationmentioning
confidence: 99%